Ridge preservation following tooth extraction: a comparison between atraumatic extraction and socket seal surgery - Arab Oghli, Ayham; Steveling, Helmut (Quintessence international, 2010)
OBJECTIVE - To evaluate whether alveolar ridge resorption following tooth extraction could be prevented or reduced using absorbable collagen material impregnated with gentamicin and sealed with an autogenous soft tissue graft to stabilize the extraction clot, and to compare this with natural healing by clot formation using a classic extraction technique. - - - METHOD AND MATERIALS - A total of 125 patients providing 173 extraction sites were included in the study. Three extraction protocols were compared: atraumatic extraction (group A, n = 101 extraction sites), atraumatic extraction sealing the socket with autogenous soft tissue graft (group B, n = 39), and atraumatic extraction with socket seal surgery and collagen matrix impregnated with gentamicin (group C, n = 33). Silicone impressions were made before and 3 months after extraction. Casts were used to measure the width of the alveolar bone at the extraction area using the incisal edge of the adjacent teeth as a reference point. - - - RESULTS - The clinical measurement 3 months after extraction revealed a loss of bone width of 0.3 +/- 0.5 mm in group A, 0.8 +/- 0.7 mm in group B, and 0.1 +/- 0.1 mm in group C. There was no significant difference in bone resorption in extraction sites among the groups (P > .05). However, the difference between group A and group C was borderline significant (P = .07). After 10 days, 31 grafts from group C and 30 grafts from group B remained vital. - - - CONCLUSIONS - It seems that extraction technique affects alveolar bone resorption, regardless of whether the socket is treated with free gingival graft or bone graft. Further, the local application of gentamicin presented more vascular ingrowth in the blood clot and granulation tissue beneath the graft, thereby supplying better nourishment during the initial healing phase of the graft.
Gesehen am 05.07.2023